2015
DOI: 10.1523/jneurosci.3655-14.2015
|View full text |Cite|
|
Sign up to set email alerts
|

Sox2 Sustains Recruitment of Oligodendrocyte Progenitor Cells following CNS Demyelination and Primes Them for Differentiation during Remyelination

Abstract: The Sox family of transcription factors have been widely studied in the context of oligodendrocyte development. However, comparatively little is known about the role of Sox2, especially during CNS remyelination. Here we show that the expression of Sox2 occurs in oligodendrocyte progenitor cells (OPCs) in rodent models during myelination and in activated adult OPCs responding to demyelination, and is also detected in multiple sclerosis lesions. In normal adult white matter of both mice and rats, it is neither e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
102
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 62 publications
10
102
0
3
Order By: Relevance
“…Activation of adult OPC proliferation by upregulation of the transcription factor SOX2 is required for efficient remyelination (Zhao et al, 2015). Because failure to remyelinate has been attributed to impaired activation of OPC proliferation (Wolswijk, 1998; Morris et al, 1994; Dowling et al, 1997), this process may also occur in chronic MS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of adult OPC proliferation by upregulation of the transcription factor SOX2 is required for efficient remyelination (Zhao et al, 2015). Because failure to remyelinate has been attributed to impaired activation of OPC proliferation (Wolswijk, 1998; Morris et al, 1994; Dowling et al, 1997), this process may also occur in chronic MS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Dcx was expressed in a significantly higher number of OL-NG2 cells than A-NG2 cells, and remained expressed in many IM-and PM-OLs, which suggests that Dcx expression is associated with NG2 cell differentiation to OLs, but not to astrocytes. Since Sox genes are crucial players in remyelination (Duncan et al, 2017;Zhao et al, 2015), and Sox2 expression was significantly increased in IM-and PM-OLs compared with M-OLs, a similar Trpv4-dependent mechanism could take part in the process of OLs maturation. A possible explanation could rise from the observation of Masuyama et al (2008) and Muramatsu et al (2007), who found that Trpv4 mediates Ca 21 -dependent terminal differentiation of osteoclasts and chondrocytes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Muramatsu et al (2007) showed that activation of Trpv4 triggers the expression of Sox genes, which consequently induces chondrogenesis. Since Sox genes are crucial players in remyelination (Duncan et al, 2017;Zhao et al, 2015), and Sox2 expression was significantly increased in IM-and PM-OLs compared with M-OLs, a similar Trpv4-dependent mechanism could take part in the process of OLs maturation. The significant difference between M-OLs 1 and 2 is the expression of Gria2, of which the protein product GluA2 renders AMPA receptors impermeable for Ca 21 (Spitzer et al, 2016;Wright & Vissel, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within populations of NG2-glia located in the same region there also appears to be considerable heterogeneity, with some studies suggesting that NG2-glia can be divided into distinct functional subtypes, such as those with differences in electrophysiological responses [28] or mitotic behaviour [14]. Underlying this are likely differences in protein expression, such as the neural stem cell-associated transcription factor Sox2, which may be associated with a proliferative state [11, 29], and the G-protein-coupled receptor GPR17, which may delineate a population with reduced proliferation and propensity to differentiate [30]. …”
Section: Introduction To Ng2-gliamentioning
confidence: 99%